«The historical cinema» as a genre of cinematography (Eurasian Journal of Philology Science and Education, 2016)
The article is about «The historical cinema» as a genre of cinematography . Its main directions, the inception of the genre, as well as evolution. With special attention we investigate the nature of the hero of the revolution in cinema 50s – 70s. Historical and revolutionary genre collaboration with the filmmakers of the socialist countries, have played a significant role in the creation of this genre. Historic film in search of art, meaningful tasks and aesthetic views – step by step transformation.It uses historical film in search of art, meaningful tasks and aesthetic views – gradual transformation. The historical event or some figure of the time, which is shown in the movie above the genre. Division game film into groups and splitting them into categories. Film genre theory, complex evolutionary path that has been passed from simple loans of paintings and archaeological reconstructions to the system of modern film language. Hero of historical and revolutionary, historical and biographical films. Main mainstream of Soviet cinema, including Kazakh and Central Asian feature films.